(untitled) (Colombia Medica, 2022)
Objective: To identify pathogenic variants in an Afro-Colombian Raizal family with risk factors for glaucoma. Methods: In the present study, whole exome sequencing was performed on seven members of a Raizal family from the archipelago of San Andrés, Providencia, and Santa Catalina, in the Caribbean region of Colombia. Four of them had been diagnosed with glaucoma. In addition, two healthy volunteers from the island were included. Results: Of the 198 single nucleotide variants associated with glaucoma previously reported by the DisGeNET database, four were identified in members of the Raizal family: rs11938093, rs7336216, rs3817672, and rs983034. Furthermore, single nucleotide variant rs983034 was identified in the Wnt ligand secretion mediator gene in all family members but not in healthy volunteers. Notably, WLS dysfunctions have been linked to pathology in the trabecular meshwork of the eye. The trabecular meshwork is an important regulator of the outflow of aqueous humor that maintains intraocular pressure (intraocular pressure) at normal levels. Damage to trabecular meshwork is associated with ocular hypertension, which leads to glaucoma progression. In relation to the other single nucleotide variants identified, their presence was confirmed in some members of the Raizal family. However, it is still unclear the pathophysiological cause that associates these single nucleotide variants with glaucoma. Conclusions: It was possible to identify four non-synonymous single nucleotide variants that predict significant damage to the structure and function of genes associated with glaucoma pathology in an Afro-Colombian